Association of sugar consumption with risk of depression and anxiety: a systematic review and meta-analysis - Xiong, JiaHui; Wang, Lu; Huang, HongLu; Xiong, San; Zhang, ShiPeng; Fu, QinWei; Tang, Rui; Zhang, QinXiu (Frontiers in Nutrition, 2024)
Background Sugar consumption has increased dramatically around the world, and at the same time, the prevalence of mental illnesses such as depression and anxiety continues to increase. While previous research has explored the impact of various dietary factors on mental health, the specific impact of dietary sugar consumption on the risk of depression and anxiety disorders remains elusive. This study aimed to comprehensively assess this relationship through a systematic review and meta-analysis. Methods PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Network (CNKI), and WangFang were systematically searched for studies of the association between total dietary sugar intake and risk of depression and/or anxiety. The articles that meet the criteria are screened and included in the systematic review, and the data are extracted after assessing their quality. Stata 18.0 software was used for the meta-analysis. Results Forty studies with 1,212,107 participants were included in the analysis. Results showed that sugar intake increased the risk of depression by 21% (OR = 1.21, 95% CI: 1.14, 1.27), while the overall association between sugar intake and anxiety risk was not statistically significant (OR = 1.11, 95% CI: 0.93, 1.28). Despite high heterogeneity (I2 = 99.7%), the results were statistically significant (p < 0.000). Subgroup analyses showed that the association between sugar consumption and depression risk remains consistent across different study designs (cross-sectional, cohort, and case–control studies) and different sample sizes (<5,000, 5,000–10,000, >10,000). Women have a higher risk of depression than men (OR = 1.19, 95% CI: 1.04, 1.35). Among the different exposure measures, the Food Frequency Questionnaire (FFQ) showed the most significant effect (OR = 1.32, 95% CI: 1.08, 1.67, I2 = 99.7%, p < 0.000). The measuring tool of subgroup analysis showed that there was a significant correlation between sugar intake and risk of depression, PHQ-9 (OR = 1.29, 95% CI: 1.17, 1.42, I2 = 86.5%, p < 0.000), and CES-D (OR = 1.28, 95% CI: 1.14, 1.44, I2 = 71.3%, p < 0.000). High-quality cross-sectional and cohort studies showed a significant association between sugar intake and depression risk, with most results being robust. While the overall analysis of sugar intake and anxiety risk was not significant, some subgroups approached significance, particularly in studies with a sample size of <5,000 (OR = 1.14, 95% CI: 0.89, 1.46) and studies using the FFQ questionnaire (OR = 1.31, 95% CI: 0.90, 1.89). Conclusion Total dietary sugar consumption was significantly associated with increased risk of depression in the general population, whereas the association with risk of anxiety was not significant. Further high-quality studies are needed to verify these associations and ensure their reliability. This study highlights the impact of dietary sugar intake on mental health, identifies potentially high-risk groups through subgroup analysis, and provides new insights into the prevention of depression and anxiety. Systematic review registration CRD42024540548.